Nonlinear models for the description of the growth of early culling guinea pigs (Cavia porcellus) - Vega-Vilca, Jaime Fernando (2023)
The aim of this study was to evaluate the non-linear Gompertz, logistic, Von Bertalanffi and Richards models to find the model that best describes the growth of early culling guinea pigs. The research was carried out in a commercial farm of Peru breed guinea pigs located in the province of Huaura, Peru. Ten males and 12 females were used, which were periodically weighed from birth to 69 days. The feeding was basically with green fodder. The degree of adjustment of the non-linear models of the weight and age of the animals was evaluated through the mean square of the error (CME) and the Akaike (AIC) and Bayesian (BIC) criteria. The logistic non-linear model was the one that best described the growth of the guinea pigs fed with green forage and allowed the elaboration of the growth standard for early culling.